2013
DOI: 10.1002/msc.1055
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Home Physiotherapy Treatment in Children and Young People with Joint Hypermobility: A Qualitative Report of Family Perspectives on Acceptability and Efficacy

Abstract: Even when exercise is seen to benefit a child's well-being, families experience challenges in adhering to a physiotherapy programme for hypermobility. Therapists can utilize findings on what enhances adherence to help CYP effectively exercise in the home setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 15 publications
0
34
0
Order By: Relevance
“…Few nested studies including child participants have been reported. Examples include assessment of a home‐based exercise programme for children with cystic fibrosis and a home physiotherapy regimen for youngsters with joint hypermobility . Both report valuable child data but this is not explicitly linked with associated RCT data.…”
Section: Discussionmentioning
confidence: 99%
“…Few nested studies including child participants have been reported. Examples include assessment of a home‐based exercise programme for children with cystic fibrosis and a home physiotherapy regimen for youngsters with joint hypermobility . Both report valuable child data but this is not explicitly linked with associated RCT data.…”
Section: Discussionmentioning
confidence: 99%
“…Children with GJH are less active in sports and miss education more often in comparison with their healthy peers with normal joint mobility [Jansson et al, ]. Qualitative research with children with JHS/hEDS and their parents has identified “difficulties at school” as being one of the six main themes, when discussing symptoms prior to commencing a treatment program [Birt et al, ]. A retrospective chart audit also showed that 40% of affected children report handwriting difficulties, 24% report “problems at school,” 41% report missing time from school, and 48% were unable to participate in physical education classes as a result of their condition [Adib et al, ].…”
Section: Jhs/heds In Childhoodmentioning
confidence: 99%
“…A recent study showed that children 8–16 years with JHS/hEDS had significantly decreased participation in housework, riding a bicycle, taking part in sport or outdoor games, as assessed by the Frequency of Participation Questionnaire, in conjunction with a higher frequency of participation in non‐sporting games and a higher need to rest [Schubert‐Hajlmarsson et al, 2012]. Withdrawal from physical activity due to their condition has also been reported by children and their parents [Birt et al, ].…”
Section: Jhs/heds In Childhoodmentioning
confidence: 99%
See 1 more Smart Citation
“…Parent emotional distress influences proxy--reported HRQOL in children with newly--diagnosed JIA [95]. Family involvement can encourage adherence to home exercise programs, particularly in older adolescents [101], and parental education and involvement is essential if progress is to be maintained when managing children with chronic musculoskletal pain [5].…”
Section: Pain Assessmentmentioning
confidence: 99%